Novel insights into the quorum sensing system of Yersina enterocolitica 8081 - Ng, Yen-Kuan (2010)
Y. enterocolitica possesses an N-acyl-homoserine lactone (AHL)-dependent quorum sensing (QS) system which consists of the luxRI homologues, yenRI. The objective of this project was to increase our understanding of the QS system(s) in Y. enterocolitica by characterising the AHL-dependent system on a genus wide basis. Species-wide analysis of an Y. enterocolitica multi-strain genome database revealed an additional luxR homologue, we termed yeoR, which is present in the fully sequenced, highly virulent Y. enterocolitica 8081 strain and other USA strains but absent in UK strains. This indicates genetic differences in the QS systems of 'New World' (North America)and 'Old World' (Europe and Japan) strains of Y. enterocolitica. yeoR is an 'orphan' luxR homologue which is not associated with an adjacent luxI homologue. Consequent work described in this study focused on the Y. enterocolitica 8081 strain. LC-mass spectrometry of spent culture supernatants from Y. enterocolitica 8081 grown at 30°C identified 16 different AHLs, mainly N-(3-oxohexanoyl)-L-homoserine lactone (62.4%) and N-hexanoyl-L-homoserine lactone (27.4%). 11 of the 16 AHLs had not previously been documented for this bacterium, including N-(3-oxoheptanoyl)-Lhomo serine lactone (with an odd number of carbons in the acyl chain) which constituted 5.1 % and has rarely been documented previously. The lambda red recombinase method of mutagenesis was used for the rapid generation of QS mutants in Y. enterocolitica 8081. Seven QS mutants were generated, three were single mutants: deltayenI deltayenR and deltayeoR, three were double mutants: deltayenIyenR, deltayenIyeoR and deltayenRyeoR, and one was a triple mutant: deltayenIyenRycoR. Analysis of the QS mutants revealed that the level of AHLs synthesised at 30°C by the R mutants: deltayenR, deltayeoR and deltayenRyeoR, were similar to the wildtype while for AHL synthase mutants: deltayenI, deltayenIyenR, deltayenIycoR and deltayenIyenRyeoR, levels of AHL were greatly reduced compared with the wildtype but were not entirely abolished. Transcriptomic analysis of Y.enterocolitica 8081 wildtype and its QS mutants using microarray technology revealed many possible QS-related regulatory networks including motility, type III secretion system and High Pathogenicity Island. Microarray data, together with RQ-PCR, phenotypic studies and promoter fusion studies showed that QS is correlated with virulence regulation (expression of virF and tyeA), virulence factors (expression of yadA and invA) and maintenance of the pYVe plasmid (expression of repA and spyA), which have not been previously documented. In conclusion, this study revealed that Y. enterocolitica 8081 has a sophisticated QS system which consists of the AHL synthase, YenI and two LuxR-type regulators, YenR and Y coR working in tandem and sharing overlapping regulon. This system maybe linked to the hypervirulence in the 8081 strain but further work is needed to confirm this.